Civic Education and the Future of American Citizenship. - Busch, Elizabeth Kaufer (Lexington Books, 2012)
Lack of civic knowledge, ignorance about the U.S. Constitution, and general ambivalence about education threaten the fiber of this nation. The remedy to this malaise, advocated in various ways by a diverse group of contributors, is a well-rounded, liberal education that prepares citizens to participate in a free republic.